2016
DOI: 10.1186/s12967-016-0870-4
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation sequencing for diagnosis of thoracic aortic aneurysms and dissections: diagnostic yield, novel mutations and genotype phenotype correlations

Abstract: BackgroundThoracic aortic aneurysms and dissections (TAAD) are silent but possibly lethal condition with up to 40 % of cases being hereditary. Genetic background is heterogeneous. Recently next-generation sequencing enabled efficient and cost-effective examination of gene panels. Aim of the study was to define the diagnostic yield of NGS in the 51 TAAD patients and to look for genotype–phenotype correlations within families of the patients with TAAD.Methods51 unrelated TAAD patients were examined by either who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
45
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 48 publications
5
45
0
Order By: Relevance
“…In this cohort of 810 patients, a pathogenic or likely pathogenic variant was identified in 66 patients (8.1%). Overall, we identified a relatively low number of pathogenic or likely pathogenic variants in our H-TAD cohort compared to pre-vious studies that identified mutations in 10.3% to 35.5% (Campens et al, 2015;Lerner-Ellis et al, 2014;Poninska et al, 2016;Proost et al, 2015;Wooderchak-Donahue et al, 2015;Ziganshin et al, 2015). This wide range is likely to be explained by differences in clinical and demographic characteristics of the study populations and different inclusion criteria used for genetic testing.…”
Section: Discussionmentioning
confidence: 78%
“…In this cohort of 810 patients, a pathogenic or likely pathogenic variant was identified in 66 patients (8.1%). Overall, we identified a relatively low number of pathogenic or likely pathogenic variants in our H-TAD cohort compared to pre-vious studies that identified mutations in 10.3% to 35.5% (Campens et al, 2015;Lerner-Ellis et al, 2014;Poninska et al, 2016;Proost et al, 2015;Wooderchak-Donahue et al, 2015;Ziganshin et al, 2015). This wide range is likely to be explained by differences in clinical and demographic characteristics of the study populations and different inclusion criteria used for genetic testing.…”
Section: Discussionmentioning
confidence: 78%
“…Recently, a large cohort from Saudi‐Arabia sequenced by custom large gene panels was reported to yield 43% of clinical diagnostic findings in a consanguineous population . In addition, large gene panels have been used in disease‐specific study groups . To our knowledge, however, there have been no published reports on the clinical utility of large gene panel sequencing in a large unselected diagnostic cohort from an outbred population.…”
Section: Introductionmentioning
confidence: 99%
“…11 In addition, large gene panels have been used in disease-specific study groups. 12,13 To our knowledge, however, there have been no published reports on the clinical utility of large gene panel sequencing in a large unselected diagnostic cohort from an outbred population. In this report, we aim to share our experience from the first 1.5 years of large gene panel sequencing in a clinical setting, which involved 501 cases.…”
Section: Introductionmentioning
confidence: 99%
“…While there are many risk factors, including male sex, age>65 years, hypertension, smoking, and syndromic disorders (such as Marfan syndrome and Loeys‐Dietz syndrome), genetic causes may be the primary cause . The identification of specific genotypes in AD could help improve the surveillance and treatment of patients, establish an anticipated risk stratification and prognosis, and perform cascade screenings for other family members at risk, all with the aim of reducing morbidity and mortality . In this study, we sequenced 142 AD‐associated genes from 72 patients with AD.…”
Section: Discussionmentioning
confidence: 99%